Survival of HIV-infected patients in the intensive care unit in the era of highly active antiretroviral therapy. Issue 11 (21st May 2007) - Dickson, S J; Batson, S; Copas, A J; Edwards, S G; Singer, M; Miller, R F
Abstract : Background: Several studies have described improved outcomes for HIV-infected patients admitted to the intensive care unit (ICU) since the introduction of highly active antiretroviral therapy (HAART). A study was undertaken to examine the outcome from the ICU for HIV-infected patients and to identify prognostic factors. Methods: A retrospective study of HIV-infected adults admitted to a university affiliated hospital ICU between January 1999 and December 2005 was performed. Information was collected on patient demographics, receipt of HAART (no patient began HAART on the ICU), reason for ICU admission and hospital course. Outcomes were survival to ICU discharge and to hospital discharge. Results: 102 patients had 113 admissions to the ICU; HIV infection was newly diagnosed in 31 patients. Survival (first episode ICU discharge and hospital discharge) was 77% and 68%, respectively, compared with 74% and 65% for general medical patients. ICU and hospital survival was 78% and 67% in those receiving HAART, and 75% and 66% in those who were not. In univariate analysis, factors associated with survival were: haemoglobin (OR = 1.25, 95% CI 1.03 to 1.51, for an increase of 1 g/dl), CD4 count (OR = 1.59, 95% CI 0.98 to 2.58, for a 10-fold increase in cells/µl), APACHE II score (OR = 0.51, 95% CI 0.29 to 0.90, for a 10 unit increase) and mechanical ventilation (OR = 0.29, 95% CI 0.10 to 0.83). Conclusions: The outcome for HIV-infected patients admitted to the ICU was good and was comparable to that in general medical patients. More than a quarter of patients had newly diagnosed HIV infection. Patients receiving HAART did not have a better outcome.